HUBUNGAN KONSUMSI FAST FOOD DAN AKTIVITAS FISIK DENGAN KEJADIAN OVERWEIGHT PADA SISWA DI SMAN 2 BANGKINANG KOTA - Syafriani, Syafriani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Overweight has become a global pandemic around the world and declared by the World Health Organization (WHO) as the largest chronic health problem. Overweight or known as obesity is a problem that is quite worrying among adolescents. This study aims to determine the relationship of fast food consumption and physical activity with the incidence of overweight in students at SMAN 2 Bangkinang Kota. The type of research used is quantitative research with cross sectional design. The population used was all students of class X and XI IPA SMAN 2 Bangkinang City totaling 420 people. Sampling in this study used stratified random sampling with a sample size of 65 people. Data analysis was done by univariate and bivariate with chi-square test and Fisher Exact. The results showed that 66.2% of respondents were overweight. The proportion of overweight is more prevalent among respondents who consume fast food (56.9%) compared to those who rarely consume fast food (9.2%). This shows that there is a significant relationship between the consumption of fast food and the incidence of overweight where P = 0,000 [(90% CI (13.21), (3.81), (45.87)]. overweight does mild physical activity by 30.8%. There is no relationship between physical activity and the incidence of overweight where P = 0.71 [(90% CI (0.51), (0.097), (2.72)]. The conclusion of this study is that there is a relationship between consumption of fast food with the incidence of overweight, while physical activity has no relationship with the incidence of overweight. It is hoped that the next researcher will study more complex using different research designs